LEARNING MATHEMATICS IN THE INCLUSIVE CLASSROOM: SLOW LEARNER STUDENTS'S DIALOGUE IN A DISCUSSION - Kusumawati, Elli; Purwanto, Purwanto; As'ari, Abdur Rahman; Irawati, Santi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The involvement of students with special needs is demonstrated by dialogue in study groups in mathematics learning in inclusive classes. Therefore, the teacher must consider forming groups to create this dialogue. Based on the results of observations, the obstacles that occur in the involvement of students with special needs in the group discussion process, according to respondents, are that not all group members understand ABK students, the speed of ABK students in absorbing information is slower, and the lack of communication between ABK and non-ABK friends. This article aims to: 1) describe the dialogue that occurs between ABK students Slow Learner with the teacher at the beginning and end of learning activities, as well as dialogue with colleagues in study groups in core activities; 2) know the characteristics of study groups that help ABK students Slow Learner understand the material in class. The research subject was a class VII ABK Slow Learner student at SMPN 14 Banjarmasin. Research findings show that ABK demonstrates verbal dialogue in class and group discussions. ABK students tend to pay attention to their friends' answers and repeat them. Apart from dialogue in verbal form, ABK students show gestures to show their involvement in the discussion. In forming groups, the teacher considers colleagues who have been sitting close to ABK as group friends for ABK. The choice of gender in group formation is also a consideration for the teacher. Study groups of male and female students allow ABK to interact more actively. The involvement of students with special needs is demonstrated by dialogue in study groups in mathematics learning in inclusive classes. Therefore, the teacher must consider forming groups to create this dialogue. Based on the results of observations, the obstacles that occur in the involvement of students with special needs in the group discussion process, according to respondents, are that not all group members understand ABK students, the speed of ABK students in absorbing information is slower, and the lack of communication between ABK and non-ABK friends. This article aims to: 1) describe the dialogue that occurs between ABK students Slow Learner with the teacher at the beginning and end of learning activities, as well as dialogue with colleagues in study groups in core activities; 2) know the characteristics of study groups that help ABK students Slow Learner understand the material in class. The research subject was a class VII ABK Slow Learner student at SMPN 14 Banjarmasin. Research findings show that ABK demonstrates verbal dialogue in class and group discussions. ABK students tend to pay attention to their friends' answers and repeat them. Apart from dialogue in verbal form, ABK students show gestures to show their involvement in the discussion. In forming groups, the teacher considers colleagues who have been sitting close to ABK as group friends for ABK. The choice of gender in group formation is also a consideration for the teacher. Study groups of male and female students allow ABK to interact more actively.